Correction of Anterior Vertical Dysplasia by using Tongue Crib Therapy in An Adult Patient -A Case Report - Mishra, Kratika; Bhardwaj, Amit (Orthodontic Journal of Nepal, 2019)
A female patient of 26 years reported to the Department of Orthodontics, with a chief complaint of spacing between upper and lower front teeth. Patient has a habit of thumb sucking during night time since last 24 years. On extra oral examination she has mesoprosopic facial form, competent lips, bilaterally asymmetric face, convex profile, acute nasolabial angle, high clinical FMA. Intra oral examination reveals anterior open bite with Angle’s Class I molar relation and class I canine relation, proclined upper and lower anterior teeth slightly crowded. Cephalometrically skeletal class II malocclusion, vertical growth pattern with bidental proclination with 10 mm openbite. Detailing treatment strategies such as bracket repositioning, occlusal adjustment, and elastics were used